BERPIKIR GEOMETRI LEVEL VISUALISASI SISWA SEKOLAH MENENGAH PERTAMA MELALUI TOPIK SEGIEMPAT MENURUT TEORI VAN HIELE - Harun Abdul Rohman; Dadang Juandi; Al Jupri (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
This research aims to describe the level of geometric thinking and geometric thinking processes of Junior High School students according to van Hiele's level of thinking on the topic of quadrilaterals. The qualitative approach is the research method used in this study through a case study method by testing the Van Hiele Geometry Test (VHGT) which was adapted from Usiskin's CDASSG and conducting interviews about the thinking process in the form of identifying, defining, and classifying which was adapted from the interview guide of Burger and Shaughnessy (1986). The subjects of this study were 297 grade VII and VIII students from two schools located in the Lembang sub-district. The results of the VHGT test showed that there were 81 students counting level 0 (visualization). The results showed that the students of class VII and VIII level 0 were as follows: 1) students were able to recognize the types of quadrangle but still affected by the prototype, 2) students were not able to classify quadrilaterals, and 3) overall description of the geometric thinking process level 0 in the form of identifying, defining, and classifying aspects according to van Hiele's thinking characteristics in general.